2018
DOI: 10.1038/s41419-018-1093-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-146b promotes cell proliferation and increases chemosensitivity, but attenuates cell migration and invasion via FBXL10 in ovarian cancer

Abstract: Epithelial ovarian carcinoma (EOC) is the most lethal gynecologic malignancy. However, the molecular mechanisms remain unclear. In this study, we found that miR-146b was downregulated in EOC and its expression level was negatively correlated with the pathological staging. Follow-up functional experiments illustrated that overexpression of miR-146b significantly inhibited cell migration and invasion, and increased cell proliferation, but it also improved the response to chemotherapeutic agents. Mechanistically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…In advanced cancer stages (III/IV), the level of miR-146b-5p expression was lower compared to earlier stages (I/II) [56]. In the cell line study, overexpression of miR-146b-5p enhanced ovarian cancer cell sensitivity to PAC and CIS [56]. Thus, miR-146b-5p downregulation seems to play a role in the resistance of ovarian cancer to cytotoxic drugs, especially to PAC.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In advanced cancer stages (III/IV), the level of miR-146b-5p expression was lower compared to earlier stages (I/II) [56]. In the cell line study, overexpression of miR-146b-5p enhanced ovarian cancer cell sensitivity to PAC and CIS [56]. Thus, miR-146b-5p downregulation seems to play a role in the resistance of ovarian cancer to cytotoxic drugs, especially to PAC.…”
Section: Discussionmentioning
confidence: 82%
“…Further studies report that low level of miR-146b-5p expression correlates with ovarian cancer progression. In advanced cancer stages (III/IV), the level of miR-146b-5p expression was lower compared to earlier stages (I/II) [56]. In the cell line study, overexpression of miR-146b-5p enhanced ovarian cancer cell sensitivity to PAC and CIS [56].…”
Section: Discussionmentioning
confidence: 85%
“…In advanced cancer stage (III/IV) the level of miR-146b-5p expression was lower compared to earlier stage (I, II) [62]. In cell line study overexpression of miR-146b-5p enhanced ovarian cancer cell sensitivity to PAC and CIS [62]. Thus, miR-146b-5p downregulation seems to play a role in resistance of ovarian cancer to cytotoxic drugs, especially to PAC.…”
Section: Discussionmentioning
confidence: 86%
“…Further studies report that low level of miR-146b-5p expression correlates with ovarian cancer progression. In advanced cancer stage (III/IV) the level of miR-146b-5p expression was lower compared to earlier stage (I, II) [62]. In cell line study overexpression of miR-146b-5p enhanced ovarian cancer cell sensitivity to PAC and CIS [62].…”
Section: Discussionmentioning
confidence: 89%
“…Also, FBXL10 was the direct target of miR-146b in regulating ovarian cancer cell proliferation, migration and invasion (12). Moreover, there were reports showed that miR-146b could regulate MyD88 expression in the proinflammatory response (13,14).…”
Section: Introductionmentioning
confidence: 99%